Volatile and non-volatile nano-electromechanical switches fabricated in a CMOS-compatible silicon-on-insulator foundry process - Yingying Li; Simon J. Bleiker; Elliott Worsey; Maël Dagon; Pierre Edinger; Alain Yuji Takabayashi; Niels Quack; Peter Verheyen; Wim Bogaerts; Kristinn B. Gylfason; Dinesh Pamunuwa; Frank Niklaus (Microsystems & Nanoengineering)
Abstract Nanoelectromechanical (NEM) switches have the advantages of zero leakage current, abrupt switching characteristics, and harsh environmental capabilities. This makes them a promising component for digital computing circuits when high energy efficiency under extreme environmental conditions is important. However, to make NEM-based logic circuits commercially viable, NEM switches must be manufacturable in existing semiconductor foundry platforms to guarantee reliable switch fabrication and very large-scale integration densities, which remains a big challenge. Here, we demonstrate the use of a commercial silicon-on-insulator (SOI) foundry platform (iSiPP50G by IMEC, Belgium) to implement monolithically integrated silicon (Si) NEM switches. Using this SOI foundry platform featuring sub-200 nm lithography technology, we implemented two different types of NEM switches: (1) a volatile 3-terminal (3-T) NEM switch with a low actuation voltage of 5.6 V and (2) a bi-stable 7-terminal (7-T) NEM switch, featuring either volatile or non-volatile switching behavior, depending on the switch contact design. The experimental results presented here show how an established CMOS-compatible SOI foundry process can be utilized to realize highly integrated Si NEM switches, removing a significant barrier towards scalable manufacturing of high performance and high-density NEM-based programmable logic circuits and non-volatile memories.